The field strength necessary for the formation of blue jets in the middle atmosphere - Panarin, Victor A.; Skakun, Victor S.; Tarasenko, Viktor Fedotovich; Sosnin, Eduard A. (Atmospheric and oceanic optics)
The formation of blue jets in air at low pressures is simulated using an apokamp discharge. The field strength is measured in the discharge channel. Assuming the applicability of similarity laws to gas discharges, the field strength in a storm cloud during the formation of blue jets is assessed to be from 6 x 1010 to 1.9 x 109 V/m, which is much higher than the values characteristic of the development of cloud-to-ground lightning discharges. A hypothesis is suggested that excess magnitudes of characteristic fields is among features of high-voltage pulsed discharge within a cloud, which results in the formation of blue jets at altitudes of about 12-18 km